Klasifikasi Pasien Kanker Payudara Menggunakan Metode Rough Set - M Rifai; Musdalifah, S; Lusiyanti, D (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2019)
ABSTRACTBreast cancer is a condition where the cell has lost control and its normal mechanism, so that abnormal growthoccurs quickly and uncontrollably that occurs in breast tissue. The basic thing that needs to be known about thecancer is the stage, so that the handling of the patient can be done correctly. In determining the cancer stage Union for International Cancer Control (UICC) uses several indicators, namely, the primary tumor which describes the size of the tumor and the expansion of the tumor to the chest wall, involvement of lymph nodes around the breast and distant metastases to other organs. Therefore, it is necessary to have a decision support system application that aims to classify cancer patient data based on the Stadium. One classification method that looks for the Decision Rule is the Rough Set. Basically this Rough set method is a decision-making method that is used to find a pattern from the data set that is processed. So that a pattern / rule can be obtained that can be used as a reference in decision making. In this study the pattern obtained as many as 16 will be entered into the Net-Bean software with java language so that it becomes a decision support system, then the system will be tested using 135 test data From these tests, namely by comparing the actual data with the results obtained from the decision support system application. So, the accuracy is 100%.Keywords : Classification, Breast Cancer Stadium, Rough Set.